PERBAIKAN APRON DAN TAILSTOCK PADA MESIN BUBUT DOALL - Febrianto, Muhammad Yori; Wibowo, Kasih; Ramli, Ramli; Hasdiansah, Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
A lathe machine is one of the primary machine tools used in manufacturing processes, which rotates a workpiece to facilitate cutting operations with the aid of a cutting tool. The apron and tailstock components on the DoAll Lt. 13 No 03 lathe play a crucial role in maintaining precision and ensuring smooth turning operations. The apron functions to control the automatic movement of the cutting tool along the longitudinal and transverse axes, while the tailstock provides additional support for the workpiece, especially during long turning operations or drilling. Common issues with the apron include wear on the lead screw, whereas the tailstock often experiences misalignment and wear on the bushing thread of the spindle. This study was conducted to repair these damages through disassembly, cleaning, visual inspection, measurement, replacement of damaged components, and realignment. The repair results showed improved machine performance in terms of movement precision and operational stability. By performing regular maintenance and repairs, the lathe machine’s working efficiency can be sustained over the long term.